2020
DOI: 10.3892/mco.2020.2112
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of progression to oral cancer in patients with dysplasia: A systematic review

Abstract: Identifying oral dysplastic lesions with a high risk of malignant transformation may create opportunities for early therapeutic interventions. Several tissue biomarkers have been suggested to date as prognostic indicators of the progression of dysplastic lesions to oral cancer. We herein present a systematic review (PROSPERO CRD42018086476), with the aim of identifying, evaluating and summarizing evidence on prognostic biomarkers of progression to oral cancer in patients with dysplasia. A search through MEDLIN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 37 publications
1
10
1
Order By: Relevance
“…42 Considering that this protein is not present at high levels in the oral mucosa, ALDH1 may represent a therapeutic opportunity for preventing the progression to oral cancer in patients with dysplasia. 43 In the present of OED cases had positive ALDH1 expression, unlike the findings of Liu et al and Visus et al where ALDH1 expression was found in only 38.3% and 32.5% of OED patients, respectively. 44,45 This suggests the role of ALDH1 in the stepwise transformation of OED to carcinomas, since various studies have suggested that ALDH1 expression is a predictive marker for the malignant transformation of OED.…”
Section: Discussioncontrasting
confidence: 67%
“…42 Considering that this protein is not present at high levels in the oral mucosa, ALDH1 may represent a therapeutic opportunity for preventing the progression to oral cancer in patients with dysplasia. 43 In the present of OED cases had positive ALDH1 expression, unlike the findings of Liu et al and Visus et al where ALDH1 expression was found in only 38.3% and 32.5% of OED patients, respectively. 44,45 This suggests the role of ALDH1 in the stepwise transformation of OED to carcinomas, since various studies have suggested that ALDH1 expression is a predictive marker for the malignant transformation of OED.…”
Section: Discussioncontrasting
confidence: 67%
“…3 Graphic representation of survivin, CDKN2A, EGFR, PLK1, p63, p40, CCND1 and BCL2 protein expression in comparison with low-and high-grade dysplasia who showed that about 50% of premalignant lesions had survivin overexpression [39]. The identification of lesions with an increased risk of transformation to oral cancer remains a clinical struggle, which, if resolved, would improve early interventions, reducing cancer-related mortality and morbidity [40]. Thus, the changes that a normal cell undergoes as it becomes malignant area matter of great interest.…”
Section: Discussionmentioning
confidence: 99%
“…3 Despite the progress in cancer diagnosis and surgical treatment, the 5-year survival rate of OSCCs remains unfavorable ($50%). 5 Thus, identifying reliable biomarkers to classify oral dysplastic lesions with a high risk of malignant transformation would establish opportunities for early therapeutic interventions. 5 Epigenetic alterations, such as DNA and RNA methylation, histone protein modification, and microRNA dysregulation, have been reported to contribute to the tumorigenesis of OSCCs.…”
Section: Introductionmentioning
confidence: 99%
“…5 Thus, identifying reliable biomarkers to classify oral dysplastic lesions with a high risk of malignant transformation would establish opportunities for early therapeutic interventions. 5 Epigenetic alterations, such as DNA and RNA methylation, histone protein modification, and microRNA dysregulation, have been reported to contribute to the tumorigenesis of OSCCs. 6 N6-methyladenosine (m6A), methylated at the N6 position of adenosine, is one of the most common and abundant RNA modifications in humans.…”
Section: Introductionmentioning
confidence: 99%